Finance and Development, March 2014. (Finance and Development; Finance and Development ;, 2014)
This chapter highlights various ways Asia's growth has affected the world economy. The chapter also shows that if currency trends continue, the Asian economy is expected to be larger than that of the United States and Europe combined. Some Asian countries offer sophisticated financial markets and are centers for technological innovation, while others are largely agricultural. The study shows that the region is home to 700 million poor people, about 65 percent of the world's poor-a figure that stands in stark relief against Asia's economic strength and growing prosperity. The chapter also references the inquiry by the managing editor of the Journal of Economic Perspectives into the rich and sometimes tortured relationship between economics and virtue.